Penciptaan Kriya Kayu Hiasan Dinding Karakter Tari Topeng Malangan dengan Teknik Ukir - Riyan Januar Nst; Sri Wiratma (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The creation of this work was motivated by the author's interest in making wall decoration wooden craft artworks inspired by the Malangan Mask dance characters. The author found unique and interesting things about the Malangan Mask dance characters such as facial expressions, eye expressions and different mask characteristics. This research aims to realize cultural, ethnic, artistic, social and philosophical visualization. The Creation Method used in the creation of wooden crafts for wall decoration of Malangan Mask dance characters by Nirwana and Andito (2017), namely starting from the internalization of ideas, the formulation of the concept of creation and the execution of the creation of works of art. The creation of this wall decoration is embodied in 12 works. The 12 wall decoration works have the same size of 25 cm x 52.8 cm. In this case, the author will create a wooden craft work hanging the wall of the Malangan Mask dance character using carving techniques. The characters of the Malangan Mask dance that will be applied include: (1) Panji Asmorobangun (Side 1), (2) Panji Asmorobagun (Side 2), (3) Dewi Sekartaji (Side 1), (4) Dewi Sekartaji (Side 2), (5) Raden Gunung Sari (side 1), (6) Raden Gunung Sari (side 2), (7) Dewi Ragil Kuning (Side 1), (8) Dewi Ragil Kuning (Side 2), (9) Klana Sewandana (Side 1), (10) Sewandana Clan (Side 2), (11) Bapang Joyo Pangangun Angun (Side 1), (12) Bapang Joyo Pangangun Angun (Side 2).